International Baccalaureate as a litmus test revealing conflicting values and power relations in the Israeli education system. Issue 2 (3rd March 2016) - Yemini, Miri; Dvir, Yuval
Abstract : This study comprises a comprehensive attempt to reveal the power relations and conflicting interests within the local–global nexus of the Israeli public education system. The perceptions of different stakeholders were explored, in regard to the implementation of the International Baccalaureate Diploma Program as an example of a globally oriented curriculum. Vignette scenarios and mixed methods were utilized in order to survey various stakeholders including parents, school principals, Education Ministry officials, academics, and educational entrepreneurs. Findings indicate that the Israeli education system is somewhat trapped between different and opposing pressures that force transformations in conflicting directions. The Israeli case may serve as a reference point for future research, advancing the study of power relations and tensions between different values and diverse stakeholders in modern education systems, especially within societies engaged in active conflict.